2007
DOI: 10.1210/jc.2006-1869
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect ofl-Thyroxine on Cardiovascular Risk Factors, Endothelial Function, and Quality of Life in Subclinical Hypothyroidism: Randomized, Crossover Trial

Abstract: SCH treated by L-thyroxine leads to a significant improvement in CV risk factors and symptoms of tiredness. The CV risk factor reduction is related to the increased level of achieved free T(4) concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
318
6
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(360 citation statements)
references
References 38 publications
17
318
6
19
Order By: Relevance
“…6 Hypothyroidism may also lead to endothelial dysfunction, hypercoagulability, impaired fibrinolysis, hyperhomocysteinemia, systemic inflammation, and platelet abnormalities. 6 Importantly, many of the aforementioned alterations are reversible upon normalization of thyroid function 7 and may be observed even in patients with physiological variations of TSH 8 and fT4. 9 Whether these same notions hold true for fT3 as well has not been established, but in our population the prevalence of hypercholesterolemia and arterial hypertension did not vary according to fT3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 Hypothyroidism may also lead to endothelial dysfunction, hypercoagulability, impaired fibrinolysis, hyperhomocysteinemia, systemic inflammation, and platelet abnormalities. 6 Importantly, many of the aforementioned alterations are reversible upon normalization of thyroid function 7 and may be observed even in patients with physiological variations of TSH 8 and fT4. 9 Whether these same notions hold true for fT3 as well has not been established, but in our population the prevalence of hypercholesterolemia and arterial hypertension did not vary according to fT3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…64 -66 Lipid profile changes are also evident in subclinical hypothyroidism. Specifically, some studies have demonstrated that LDL is increased in subclinical hypothyroidism and reversible with thyroid hormone replacement, 67,68 whereas other studies have shown increased total cholesterol in subclinical hypothyroidism with no changes in LDL. The reported mechanisms for the development of hypercholesterolemia in hypothyroidism include decreased fractional clearance of LDL by a reduced number of LDL receptors in the liver in addition to decreased receptor activity.…”
Section: Thyroid Hormone Effects On Lipid Metabolismmentioning
confidence: 99%
“…65,66 Lipid metabolism is altered in subclinical hypothyroidism. 64,67 Patients have increased serum lipid levels, and cholesterol levels appear to rise in parallel with serum TSH. 7,66 C-Reactive protein, a risk factor for heart disease, is increased in subclinical hypothyroidism.…”
Section: Subclinical Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Razvi et al 11 have recently suggested that L-T4 replacements improve cardiovascular risk factors and endothelial function in subclinical hypothyroidism. However, it is still not clear whether the normalization of subclinical thyroid dysfunction leads to a change in blood pressure.…”
mentioning
confidence: 99%